“Anti-Condensation” Aluminum Superhydrophobic Surface by Smaller Nanostructures - Li, Kangning; Zhao, Ying; Yang, Jintao; Feng, Jie (Frontiers in Bioengineering and Biotechnology, 2022)
According to classical heterogeneous nucleation theory, the free energy barrier (Gc) of heterogeneous nucleation of vapor condensation ascends dramatically as the substrate nanostructure diameter (Rs) decreases. Based on this idea, here we fabricated two types of superhydrophobic surfaces (SHSs) on aluminum substrate by different roughening processes and same fluorization treatment. Water vapor condensation trials by optical microscope and ESEM confirmed that on SHSs with submicron rectangle structures, typical self-propelled motion of condensates or jumping condensation occurred. However, on SHS with coral like micro/nano- structures, vapor nucleation occurred tardily, randomly and sparsely, and the subsequent condensation preferentially occurred on the nuclei formed earlier, e.g., the condensation on such SHS typically followed Matthew effect. Higher vapor-liquid nucleation energy barrier caused by smaller fluorinated nanostructures should be responsible for such unique “anti-condensation” property. This study would be helpful in designing new SHSs and moving their application in anti-icing, antifogging, air humidity control, et al.